Potential of boron neutron capture therapy (BNCT) for malignant peripheral nerve sheath tumors (MPNST). (December 2015) - Fujimoto, Takuya; Andoh, Tooru; Sudo, Tamotsu; Fujita, Ikuo; Fukase, Naomasa; Takeuchi, Tamotsu; Sonobe, Hiroshi; Inoue, Masayoshi; Hirose, Tkanori; Sakuma, Toshiko; Moritake, Hiroshi; Sugimoto, Tohru; et al.
Abstract: Malignant peripheral nerve sheath tumors (MPNST) are relatively rare neoplasms with poor prognosis. At present there is no effective treatment for MPNST other than surgical resection. Nonetheless, the anti-tumor effect of boron neutron capture therapy (BNCT) was recently demonstrated in two patients with MPNST. Subsequently, tumor-bearing nude mice subcutaneously transplanted with a human MPNST cell line were injected with p -borono-L -phenylalanine (L -BPA) and subjected to BNCT. Pathological studies then revealed that the MPNST cells were selectively destroyed by BNCT. Highlights: MPNST responds to no effective treatment method other than surgery. Two clinical cases of MPNST demonstrated the efficacy of BNCT. MPNST cells and the MPNST-bearing animal model showed high uptake of boron. The results demonstrated the efficacy of BNCT for MPNST.